Transplacental passage of vancomycin. (18th April 2018) - Towers, Craig V.; Weitz, Beth
Abstract: Objective: To evaluate a larger number of patients receiving a vancomycin-dosing regimen of 20 mg/kg IV every 8 h for Group B streptococcus (GBS) chemoprophylaxis and analyze maternal and neonatal cord blood levels at delivery. Methods: We prospectively enrolled every mother that entered labor with a positive GBS culture and a high-risk penicillin allergy with resistance to clindamycin or unknown sensitivity. Maternal and cord blood vancomycin levels were obtained at delivery. Time from last dose completion to delivery, number of doses administered and body mass index were assessed. Results: A total of 30 patients consented and 23 (77%) maternal levels and cord blood levels were therapeutic. There were eight patients where one or both maternal and/or cord blood values were non-therapeutic, but in six of these, there was a regimen violation regarding timing of the next dose or total dosage administered. Of the 24 patients where the regimen was correctly followed, 22 (92%) had therapeutic maternal and cord blood levels. Conclusions: Using a vancomycin-dosing regimen of 20 mg/kg IV every 8 h (maximum individual dose of 2 g) produces therapeutic levels in more than 75% of mother/newborn pairs and this can exceed 90% when dosing regimens are correctly followed.